Evolution of physical, chemical, and biological attributes of hydromorphic soil under crop-livestock integration systems in the Pampa biome - Carvalho, Juliana dos Santos; Kunde, Roberta Jeske; Stöcker, Cristiane Mariliz; Lima, Ana Cláudia Rodrigues de; Silva, Jamir Luis Silva da (Pesquisa Agropecuaria Brasileira, 2016)
The objective of this work was to evaluate the evolution of physical, chemical, and biological attributes of a hydromorphic soil, in crop-livestock integration systems in the Pampa biome. The study was carried out in an experimental area under no-tillage system since 2006, in the municipality of Capão do Leão, in the state of Rio Grande do Sul, Brazil, in a Haplic Albaqualf. Three areas were used with the following management types: an area without grazing; a grazing area under crop-livestock integration (CLI), with soybean or corn in alternating years, in succession to winter grazing; and a native grazed field. Soil samplings were conducted in two seasons in all areas, at the 0.00–0.05, 0.05–0.10, and 0.10–0.20-m soil layers, in order to carry out the following soil analyses: physical attributes, macroporosity, microporosity and density; chemical attributes, total organic carbon, total nitrogen, and carbon/nitrogen ratio; biological attributes, diversity and abundance of edaphic macrofauna. In the grazinf area, macroporosity increase over the time. There was a reduction in soil bulk density at the 0.00–0.05-m soil depth, whereas total organic carbon increased in the 0.10–0.20-m soil depth, in all areas. The crop-livestock integration system benefits the abundance and diversity of the edaphic fauna in the soil.